Climate more important than soils for predicting forest biomass at the continental scale. Issue 11 (29th July 2020) - Bennett, Alison C.; Penman, Trent D.; Arndt, Stefan K.; Roxburgh, Stephen H.; Bennett, Lauren T.
Abstract : Above‐ground biomass in forests is critical to the global carbon cycle as it stores and sequesters carbon from the atmosphere. Climate change will disrupt the carbon cycle hence understanding how climate and other abiotic variables determine forest biomass at broad spatial scales is important for validating and constraining Earth System models and predicting the impacts of climate change on forest carbon stores. We examined the importance of climate and soil variables to explaining above‐ground biomass distribution across the Australian continent using publicly available biomass data from 3130 mature forest sites, in 6 broad ecoregions, encompassing tropical, subtropical and temperate biomes. We used the Random Forest algorithm to test the explanatory power of 14 abiotic variables (8 climate, 6 soil) and to identify the best‐performing models based on climate‐only, soil‐only and climate plus soil. The best performing models explained ~50% of the variation (climate‐only: R 2  = 0.47 ± 0.04, and climate plus soils: R 2  = 0.49 ± 0.04). Mean temperature of the driest quarter was the most important climate variable, and bulk density was the most important soil variable. Climate variables were consistently more important than soil variables in combined models, and model predictive performance was not substantively improved by the inclusion of soil variables. This result was also achieved when the analysis was repeated at the ecoregion scale. Predicted forest above‐ground biomass ranged from 18 to 1066 Mg ha −1, often under‐predicting measured above‐ground biomass, which ranged from 7 to 1500 Mg ha −1 . This suggested that other non‐climate, non‐edaphic variables impose a substantial influence on forest above‐ground biomass, particularly in the high biomass range. We conclude that climate is a strong predictor of above‐ground biomass at broad spatial scales and across large environmental gradients, yet to predict forest above‐ground biomass distribution under future climates, other non‐climatic factors must also be identified.